Sleep disorders in childhood - Alexandra-Maria Kazala; Vasiliki Karagianni; George Grammatikas (Ene, 2019)
Sleep disorders have reached epidemic rates in the modern world. It is important to note that they can affect children as well as adults. Sleep is of the utmost importance for the maintenance of body homeostasis. Many disease processes affecting sleep have been associated with numerous symptoms, including cognitive impairment, fatigue as well as a wide range of behavioral, hormonal and metabolic derangements. Sleep disorders in childhood can be classified by age of incidence (in infants, toddlers, school-age children or adolescents) and by the exact nature of the symptoms. They are classified in insomnias, hypersomnias, parasomnias, circadian rhythm disorders and respiratory disorders which affect sleep. Parasomnias are the most common sleep disorders in toddlers, with night terrors, nightmares and sleepwalking being the most common. Respiratory disorders are the most important in older children, especially obstructive sleep apnea syndrome. All sleep disorders are clinically manifested with symptoms of sleep deprivation. Their management always involves improvement of sleep hygiene, though in some cases (such as obstructive sleep apnea) specific medical treatment is also available and warranted. A three-way relationship of trust, compassion and cooperation between child, family and healthcare professional is a prerequisite for the effective management of childhood sleep disorders. Nursing staff are the main factor cultivating that relationship in the context of inpatient care.